STORY ILLUSTRATION DRAWING THEMATIC-BASED AS A MEANS OF PRESERVING A HEALTHY LIFE LITERACY FOR ELEMENTARY SCHOOL STUDENTS - Sari, Yofita (Universitas Pendidikan Indonesia, 2024)
There needs to be innovation in improving the quality of elementary school students' health awareness to help overcome health problems through education. Therefore, the researchers conducted a study entitled Thematic-based story illustrations as a means of healthy living literacy for elementary school students. The research method that will be used in this study is the ADDIE model Research And Development Method. This research will be conducted in elementary schools in Songgom Lor, Songgom District, and Brebes Regency. Researchers carry out stages (1) Analysis: needs analysis to determine the right problems and solutions to determine student competencies; (2) Design: determine specific competencies, methods, teaching materials, and learning strategies; (3) Development: produce programs and teaching materials that will be used in learning programs; (4) Implementation: carrying out learning programs by implementing learning program designs or specifications; (5) Evaluation: evaluating learning programs and evaluating learning outcomes. The research objectives include (1) theoretically examining the concept of healthy living with care for the environment; (2) developing instruments for healthy living skills with care for the environment; (3) identifying healthy living behaviors with care for the environment for elementary school students and teachers; and (4) developing thematic-based story illustrations as media for healthy living literacy.